DECISION MAKING MODEL OF DETERMINING CANDIDATES FOR CORPORATE SOCIAL RESPONSIBILITY OF AGRICULTURAL SEEDS USING WEIGHTED PRODUCTS - Ferry Susanto; M Abu Jihad Plaza R (LPPM STMIK Pringsewu, 2021)
Corporate Social Responsibility is a business commitment to act ethically, operate legally and contribute to economic improvement simultaneously with improving the quality of life of employees and their families, the local community, and society at large. Social responsibility or Corporate Social Responsibility (CSR) is a concept in which organizations, especially companies, have a responsibility to consumers, employees, shareholders, communities, and the environment in all aspects of the company's operations such as issues that have an impact on the environment such as pollution, waste, product and labor safety. CSR is not only limited to the concept of providing financial assistance to the social environment but also how companies treat their employees non-discriminatory and maintain good relationships with suppliers. Government obligation requires companies to carry out social responsibility as a form of company concern for the community. This research is conducted with the aim of determining prospective recipients of CSR for agricultural seeds using the Weighted Product (WP) method. The Weighted Product method is used because this method relates the attribute value where the value must be raised to the power of the weight value of the attribute in question. In determining the candidate for receiving CSR for agricultural seeds, there are many criteria that must be owned by the Farmer Group as a condition for obtaining CSR for agricultural seeds. The criteria used are submitting a proposal, land area, land survey and prospective farmers receiving assistance, the status of farmer groups, number of members, and farmer groups established for at least 1 year. From the research conducted, there are 20 alternatives. From the analysis of research results from manual tests and application tests, the preference for similarity of calculation results is obtained. From the calculation results through manual testing and application testing, the highest alternative results are 0.063470478 for Sidomakmur Farmer, and the lowest alternative results is 0.034660601 for Sidoluhur Farmer as the alternative chosen as the highest indicator to obtain 3 types of agricultural crops.